TEKNOLOGI ARTIFICIAL INTELLIGENCE DAN BLOCKCHAIN: SEBUAH KENISCAYAAN PADA AKUNTAN DAN AUDITOR - Rahmawati, Mia Ika; Subardjo, Anang (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2023)
The development of technology has affected dramatic changes to the practice of all professions and accountants and auditors are no exception. This research provides a comprehensive review of the development of Artificial Intelligence and Blockchain technologies and their impact specifically in the accounting and auditing profession. This research aims to explore a change in the accounting and auditing profession in following the latest technological developments and analyzing the impact of its development in the future. This research method is using a descriptive qualitative approach. The results of this study are four research themes, namely: Real-Time Accounting, Triple-Entry Accounting, Sustainable Auditing and the Changing Role of Accountants and Auditors. By considering the dramatic changes and developments of Artificial Intelligence and Blockchain in the field of accounting and auditing, this research reflects how these two technologies will affect the processes and practices of accounting and auditors to be more effective and efficient. So that accountants and auditors can focus on planning and decision making. As for further research, it can be done with a quantitative approach, namely with experimental methods on the effect of artificial intelligence and blockchain technology on the behavior of accountants and auditors.